Enhancing students' critical thinking skills through a team games tournament model - Nora, Desri Nora; Aisyah Anggraeni; Athia Rohza; Padli, Padli; Indah Muliati; Aldri Frinaldi; Fiky Zarya (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to enhance the critical thinking skills of grade XI IPS 3 students at SMA Adabiah 2 Padang in sociology lessons through the implementation of the Teams Games Tournament (TGT) model. Using the Classroom Action Research (CAR) method by Kemmis and McTaggart, the research was conducted in three cycles involving 28 students. Data were collected through observation, interviews, and documentation, and analyzed using qualitative techniques for interviews and quantitative analysis for observation results. Findings indicated a consistent improvement in students’ critical thinking skills across cycles: 39.2% in Cycle I, 57.6% in Cycle II, and 79.1% in Cycle III. The study concludes that the TGT model effectively increases student engagement and critical thinking by integrating interactive elements and a supportive learning environment.